Treatment of SARS-CoV-2 relapse with remdesivir and neutralizing antibodies cocktail in a patient with X-linked agammaglobulinaemia. (September 2021) - Palomba, Emanuele; Carrabba, Maria; Zuglian, Gianluca; Alagna, Laura; Saltini, Paola; Fortina, Valeria; Hu, Cinzia; Bandera, Alessandra; Fabio, Giovanna; Gori, Andrea; Muscatello, Antonio
ABSTRACT: During the coronavirus disease 2019 (COVID-19) pandemic, patients with humoral immunodeficiency are at higher risk of developing chronic infection and having a negative outcome. Few data are available on therapeutic options for this population. This case report discusses the treatment of disease relapse with remdesivir and monoclonal antibodies in an adult patient with X-linked agammaglobulinaemia.